PENDIDIK DAN PESERTA DIDIK PERSPEKTIF KH. HASYIM ASY'ARI - Rahmatullah, Rahmatullah; Misbah, Ahmad Fahrul (STAI Ma'had Aly Al-Hikam Malang, 2023)
Abstract: KH. Hasyim Asy'ari is a figure who contributes to the world of education, so research on his thoughts is very important and interesting to do. This study aims to analyze the essence of educators and students in KH. Hasyim Asy'ari thought. The research method uses library research. The result of this studi are the essence of educators or teachers from the perspective of KH. Hasyim Asy'ari is the person responsible for providing assistance to students in both physical and spiritual development. Meanwhile, students are members of the community who are trying to develop their own potential through a learning process that is available in certain paths, levels and types of education. The novelty of this research is being an educator and student requires self-preparedness; have good criteria for the provision of knowledge and try to practice it and have the right ethics that is in accordance with the rules or values in Islamic education.